Tingkat Pemahaman Masyarakat Terhadap Tindak Pidana (Hate Speech, Hoax) Dalam Undang-Undang Informasi Dan Transaksi Elektronik Didesa Pekuncen Kec. Sempor - Rahmad, Noor; Setiyawan, Deni; Novita, Diana; Prasojo, Radityo Dwi (Universitas Tabanan, 2023)
His study aims to examine the level of public understanding of criminal acts in the form of Hate Speech and Hoax which are regulated in the Electronic Information and Transaction Law (UU ITE). The development of information technology and the internet has had a significant impact on the way people communicate and interact. However, the use of this technology has also created new problems, such as the rise of hate speech and hoaxes on online platforms. This study uses a survey method with questionnaires distributed to respondents randomly in several areas that represent the diversity of society. The questions in the questionnaire focused on people's understanding of the concept of Hate Speech and Hoax in accordance with the ITE Law, the impact of the spread of Hate Speech and Hoax, as well as knowledge of related legal sanctions.